Pertussis vaccination status and vaccine acceptance among medical students: multicenter study in Germany and Hungary - Mandy Böhme; Karen Voigt; Erika Balogh; Antje Bergmann; Ferenc Horváth; Joachim Kugler; Jörg Schelling; Jeannine Schübel; Henna Riemenschneider (BMC, 2019)
Abstract Background Medical students are at risk of contracting and transmitting infectious diseases such as pertussis. Complete vaccination status is important to protect own, patient and public health. Knowing own vaccination status is elementary for following current vaccination recommendations, including boosters. We aimed to assess pertussis vaccination status and vaccination acceptance among medical students of different nationalities. Methods A cross-sectional multicenter health survey at German and Hungarian universities enclosed international medical students in the 1st, 3rd and 5th year of study. Self-reported data from 2655 students regarding pertussis vaccination status were analyzed. Subgroup analysis enclosed data of German (n = 1217), Hungarian (n = 960) and other nationality (n = 478) students ("other"). Results More Hungarians reported basic immunization (39.0% vs 15.8% Germans vs 24.3% others, p ≤ 0.05). Booster vaccination was reported more by Germans (60.5% vs 43.6% Hungarians vs 36.0% others, p ≤ 0.05). Germans were more likely to report being unvaccinated (3.7% vs 0.9% Hungarians, p ≤ 0.05). More medical students of other nationalities were unaware of their pertussis vaccination status (37.4% vs 20.0% Germans/ 16.5% Hungarians, p ≤ 0.05). 75.2% (n = 1931) rated pertussis vaccinations as absolutely necessary (86.2% Hungarians vs 69.8% Germans/ 66.1% others, p ≤ 0.05). Conclusions Positive attitudes towards vaccinations were reported but a large group reported insufficient vaccination status and being not aware of their status, especially among international students. Hungarians possibly have a better vaccination status than reported, based on mandatory vaccinations in childhood. The low awareness of vaccination status has implications for future booster vaccinations. All students should be informed about current recommendations and receive vaccination offers in frames of low-threshold medical services.